Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/chem.201405581
|View full text |Cite
|
Sign up to set email alerts
|

Induced Folding of Protein‐Sized Foldameric β‐Sandwich Models with Core β‐Amino Acid Residues

Abstract: The mimicry of protein-sized β-sheet structures with unnatural peptidic sequences (foldamers) is a considerable challenge. In this work, the de novo designed betabellin-14 β-sheet has been used as a template, and α→β residue mutations were carried out in the hydrophobic core (positions 12 and 19). β-Residues with diverse structural properties were utilized: Homologous β(3) -amino acids, (1R,2S)-2-aminocyclopentanecarboxylic acid (ACPC), (1R,2S)-2-aminocyclohexanecarboxylic acid (ACHC), (1R,2S)-2-aminocyclohex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…b-Sheet forming a/b-peptides were designed too [123][124][125][126][127][128]. Importantly, these structures might be useful in PPI modification where water-accessible flat surfaces play a crucial role.…”
Section: B-peptidesmentioning
confidence: 99%
“…b-Sheet forming a/b-peptides were designed too [123][124][125][126][127][128]. Importantly, these structures might be useful in PPI modification where water-accessible flat surfaces play a crucial role.…”
Section: B-peptidesmentioning
confidence: 99%
“…In protein prosthesis, 6,7 backbone engineering 8 allows individual residues or sequences within proteins to be replaced with non-natural residues. [9][10][11][12][13] Notable examples include the incorporation of b-amino acid residues in the B1 domain of Streptococcal protein G (GB1) 14 and Betabellin-14, 15 the re-engineering of a heterodimeric chorismate mutase enzyme 16 using sequence based design, the replacement of loop regions in GB1 using PEG 17 and the incorporation of an entire b-amino acid topological mimic of an a-helix into IL8. 18 a-Helix mimetics [19][20][21][22][23] employ a suitably functionalised generic scaffold to reproduce the spatial projection and composition of key side chains found at a helical interface between two proteins.…”
mentioning
confidence: 99%
“…Replacing  residues with a hydrophobic surface area similar to (1R,2S)-ACHC (1c and 1d) resulted in a high original -sheet content and a low inducibility, which highlighted the importance of the compatibility of the sidechain with the hydrophobic core. 16 The cyclic side-chain fitted into the peripheral regions of the inner core, but substitution in the centre of the tightly packed core was unfavourable (1a, 1b, 2a and 2b). It has previously been shown that appropriate orientation of the side-chains facilitates the hydrophobic interactions that play crucial roles in -sheet folding, and they are scaled up by increasing temperature.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%